Adsorbent as well as preparation method and application thereof
By using the metal organic frame material adsorbent that reacts tetravalent transition metal and 1,3,5-tribenzoic acid in a mixed solvent of DMF/formic acid and soaks through methanol, the separation problem of C2H2 and CO2 in the prior art is solved, and the problem of separation of C2H2 and CO2 is realized. The one-step separation of high-purity C2H2 and the low-energy-consuming separation effect are achieved.
Patent Information
- Application Number
- CN202410049166.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-12
- Publication Date
- 2024-12-24
AI Technical Summary
The prior art is difficult to effectively separate C2H2 and CO2 with similar physical properties, resulting in high energy consumption and low yield in the separation process. Commonly used low-temperature distillation technologies require low temperature, high pressure, high tower plate, high reflux ratio, high energy consumption, and conventional MOF The stronger affinity of the material for C2H2 leads to a low yield of high-purity C2H2.
The tetravalent transition metal and 1,3,5-tribenzoic acid react in a mixed solvent of DMF/formic acid, and soaked through methanol to form a metal organic frame material adsorbent. The adsorption capacity of the material to CO2 is greater than C2H2, realizing the CO2/C2H2 High purity C2H2 is obtained in one step in the mixed gas without further desorption process.
It has achieved a high-purity C2H2 step in the CO2/C2H2 mixed gas. The material has good cycle stability, thermal stability and acid-base stability, and has low energy consumption and efficient separation effect, replacing traditional energy-intensive technologies such as Solvent extraction or low temperature distillation.
Smart Images

Figure CN119176947A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical separation, and in particular to an adsorbent and a preparation method and application thereof. Background Art
[0002] Gaseous light hydrocarbons are very important raw materials in chemical synthesis, and their separation and purification are very important. C2H2 is a very important chemical commodity, widely used in the manufacture of vinyl and acrylic polymers. Industry generally produces C2H2 through partial oxidation and cracking of natural gas. The process does not produce an equal proportion of CO2, but the two molecules have the same kinetic diameter. and similar physical properties (boiling point: C2H2, 189.3K; CO2, 194.7K). This makes the separation of C2H2 / CO2 very difficult. The existing cryogenic distillation technology is used for the separation of C2H2 and CO2 with similar physical properties. The commonly used cryogenic distillation technology requires low temperature, high pressure, high tower plate, high reflux ratio, high energy consumption and other conditions, and the equipment is huge. Therefore, it is very important to find a separation technology with relatively low energy consumption and simple equipment process.
[0003] Adsorption separation technology has the advantages of low energy consumption, high efficiency, high product purity, simple process and simple equipment, and has a good prospect for industrial application. The core of adsorption separation technology is the adsorbent. Metal organic framework materials (MOFs), as a new generation of porous adsorption materials, have the advantages of high porosity, strong pore structure design, and uniform pore size. They show great potential in the field of adsorption separation. However, most of the excellent MOF materials reported so far show a stronger affinity for C2H2, so desorption is required to obtain C2H2, and it is difficult to obtain high-purity C2H2. Multi-stage adsorption and desorption processes are required to obtain high-purity C2H2, which leads to low yield of high-purity C2H2 and high energy consumption in the separation process. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an adsorbent and a preparation method and application thereof. In the present invention, a tetravalent transition metal and 1,3,5-tribenzoic acid are reacted in a DMF / formic acid mixed solvent, the reaction product is soaked in methanol, and a metal organic framework material adsorbent is obtained through self-assembly. The adsorbent of the present invention has a larger pore structure and better stability. The adsorption capacity of the synthesized material for CO2 is greater than that for C2H2, and the adsorption of CO2 is achieved. 2 / High-purity C2H2 can be obtained from the C2H2 mixed gas in one step without further desorption process.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A method for preparing an adsorbent comprises the following steps:
[0007] Using 1,3,5-tribenzoic acid as a ligand, tetravalent transition metal chloride oxide as a node coordination, and DMF and formic acid as a mixed solvent, a reaction is performed to obtain a slurry, and the slurry is post-treated to obtain a product;
[0008] The adsorbent is obtained by soaking the product in methanol.
[0009] In a preferred embodiment of the present invention, the tetravalent transition metal is one of Zr, Hf and Ti.
[0010] In a preferred embodiment of the present invention, the molar ratio of the tetravalent transition metal chloride oxide to 1,3,5-tribenzoic acid is 2-4:1, the volume ratio of DMF to formic acid is 1-2:1, the mass ratio of the product to the volume ratio of methanol is 0.8 g:30 mL, and the amount ratio of 1,3,5-tribenzoic acid to the mixed solvent is 1 mmol:30-45 mL.
[0011] In a preferred embodiment of the present invention, the reaction temperature is 120-140° C., the reaction time is 48-72 hours, and the methanol soaking time is 48-96 hours.
[0012] In a preferred embodiment of the present invention, the post-treatment step is: filtering the slurry and soaking it in acetone for 48 to 72 hours. The purpose of soaking in acetone is to remove DMF molecules in the structural pores, and then vacuum activation is performed.
[0013] Another object of the present invention is to provide an adsorbent prepared by any of the preparation methods described above.
[0014] The third object of the present invention is to provide an application of the above-mentioned adsorbent in the selective adsorption of CO2 to separate and purify C2H2, and the application method is: contacting the mixed gas of C2H2 and CO2 with the adsorbent material in the adsorption column, adsorbing the CO2 in the mixed gas, and obtaining C2H2 with a purity greater than 99.9%.
[0015] In a preferred embodiment of the present invention, the volume fraction of C2H2 in the mixed gas is 1% to 99%.
[0016] In a preferred embodiment of the present invention, the adsorption temperature is -50 to 150° C., the adsorption pressure is 0 to 10 bar, the desorption temperature is 25 to 150° C., and the desorption pressure is 0 to 1.0 bar.
[0017] In a preferred embodiment of the present invention, the contact mode between the mixed gas and the adsorbent is one of fixed bed adsorption, fluidized bed adsorption or moving bed adsorption, and the contact adsorption process is one or more of a single-tower or multi-tower pressure swing adsorption process, a temperature swing adsorption process, and a vacuum adsorption process.
[0018] In a preferred embodiment of the present invention, the fixed bed adsorption method is as follows: under set adsorption temperature and adsorption pressure, a mixed gas containing C2H2 and CO2 enters a fixed bed adsorption column filled with adsorbent at a set flow rate, and the C2H2 component preferentially penetrates the bed layer, and high-purity C2H2 gas is directly obtained from the outlet of the adsorption column.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention uses 1,3,5-tricarboxylic acid as a ligand, a tetravalent transition metal as a node coordination, and DMF and formic acid as a mixed solvent to form a metal organic framework (MOF-808) adsorbent through self-assembly. After a simple treatment method of methanol soaking, a MOF-808-M-Me adsorbent is obtained. The purpose of using methanol soaking is to separate the formic acid small molecules bound to the structural framework, and the vacant open metal sites are used to bind to methanol molecules, so that sites with selective binding to CO2 are generated on the surface of the framework. Due to the particularity of the treated structure, the material shows a stronger affinity for CO2, while the force on C2H2 is weakened. Based on the above-mentioned capture differences of different gas components, the present invention achieves CO 2 / High-purity C2H2 can be obtained from C2H2 mixed gas in one step without further desorption process. At the same time, the adsorbent material has good cyclic stability, thermal stability and acid-base stability. It is expected to be used as a potential physical adsorbent in industrial adsorption and separation technology fields such as high-efficiency and low-energy pressure swing adsorption, realizing the traditional energy-intensive technologies in industry such as solvent extraction or low-temperature distillation, etc., for the separation of C2H2 and CO2.
[0021] 2. The present invention obtains MOF-808-M-Me adsorbent after soaking the synthesized MOF-808-M-Ac adsorbent in methanol, and replaces the original formic acid small molecules in the pores, so that the material's ability to capture CO2 is greatly improved, and the ability to capture C2H2 is reduced, so that the adsorption capacity of CO2 is greater than that of C2H2, and it has the ability to preferentially capture CO2 from a mixed gas of CO2 and C2H2.
[0022] 3. Conventional MOFs materials adsorb more C2H2 than CO2, so CO2 can only be obtained through desorption, which has a low yield and low gas purity. Conventional MOF-808-M-Ac does not have the ability to preferentially capture CO2 in C2H2 and CO2. However, through a simple treatment method such as soaking in methanol, the formic acid molecules in the organic framework adsorbent material are replaced, and the material has the ability to preferentially capture CO2 in a mixed gas of C2H2 and CO2. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a synthetic powder image of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention;
[0024] Figure 2 This is a synthetic powder image of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention;
[0025] Figure 3 The X-ray diffraction experimental results of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention;
[0026] Figure 4 This is the X-ray diffraction experimental result of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention;
[0027] Figure 5 The adsorption isotherms of MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention for C2H2 and CO2 at 298K;
[0028] Figure 6 The adsorption isotherms of MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention for C2H2 and CO2 at 298K;
[0029] Figure 7 The dynamic penetration curve of the C2H2 / CO2 mixed gas component of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention at 298K;
[0030] Figure 8 The dynamic penetration curve of the C2H2 / CO2 mixed gas component of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention at 298K;
[0031] Fig. 9 The dynamic penetration curve of the C2H2 / CO2 mixed gas component of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention at 298K;
[0032] Fig.10The acid-base stability test results of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention;
[0033] Fig.11 This is the acid-base stability test result of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0036] The present invention takes into account that in the separation experiment of C2H2 and CO2 with similar physical properties, most of the excellent MOF materials reported so far show a stronger affinity for C2H2, so desorption is required to obtain C2H2, and it is difficult to obtain high-purity C2H2. High-purity C2H2 can only be obtained after a multi-stage adsorption and desorption process, which leads to a low yield of high-purity C2H2 and high energy consumption in the separation process. Therefore, the present invention provides an adsorbent and a preparation method and application thereof, using 1,3,5-tribenzoic acid as a ligand, a tetravalent transition metal oxychloride as a node coordination, DMF and formic acid as a mixed solvent, and reacting at 120-140°C After 48 to 72 hours, the MOF-808 adsorbent is self-assembled and soaked in methanol to obtain the adsorbent material of the present invention. The purpose of soaking in methanol is to separate the formic acid small molecules bound to the structural framework, and the vacated open metal sites are used to bind to methanol molecules, so that sites with selective binding to CO2 are generated on the surface of the framework, so that the adsorbent material of the present invention shows a stronger affinity for CO2, while the force on C2H2 is weakened, so that the adsorption capacity of CO2 is greater than that of C2H2, and ... 2 / High-purity C2H2 can be obtained from C2H2 mixed gas in one step without further desorption. At the same time, the material has good cyclic stability, thermal stability and acid-base stability. It is expected to be used as a potential physical adsorbent in industrial adsorption and separation technologies such as high-efficiency and low-energy pressure swing adsorption, realizing traditional energy-intensive technologies in industry such as solvent extraction or low-temperature distillation, etc., for the separation of C2H2 and CO2.
[0037] Example 1
[0038] A method for preparing a MOF-808-Zr-Me adsorbent comprises the following steps:
[0039] (1) 3 mmol of zirconium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 15 mL of DMF and 15 mL of formic acid, and reacted at 120°C for 72 h to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 48 h to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 h, and the product was collected and recorded as MOF-808-Zr-Ac.
[0040] (2) 0.8 g of MOF-808-Zr-Ac prepared in step (1) was soaked in 30 mL of methanol solution for 72 h, filtered and dried to obtain MOF-808-Zr-Me adsorbent.
[0041] Example 2
[0042] A method for preparing a MOF-808-Hf-Me adsorbent comprises the following steps:
[0043] (1) 3 mmol of hafnium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 15 mL of DMF and 15 mL of formic acid, and reacted at 120°C for 72 h to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 48 h to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 h, and the product was collected and recorded as MOF-808-Hf-Ac.
[0044] (2) 0.8 g of MOF-808-Hf-Ac prepared in step (1) was placed in 30 mL of methanol solution and soaked for 72 h, and then filtered and dried to obtain MOF-808-Hf-Me adsorbent.
[0045] Example 3
[0046] A method for preparing a MOF-808-Ti-Me adsorbent comprises the following steps:
[0047] (1) 3 mmol of titanium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 15 mL of DMF and 15 mL of formic acid, and reacted at 120°C for 72 h to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 48 h to remove the DMF molecules in the structural pores. The slurry was then vacuum activated at 373 K for 6 h, and the product was collected and recorded as MOF-808-Ti-Ac.
[0048] (2) 0.8 g of MOF-808-Ti-Ac prepared in step (2) was placed in 30 mL of methanol solution and soaked for 72 h, and then filtered and dried to obtain MOF-808-Ti-Me adsorbent.
[0049] Example 4
[0050] A method for preparing a MOF-808-Zr-Me adsorbent comprises the following steps:
[0051] (1) 2 mmol of zirconium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 22.5 mL of DMF and 15 mL of formic acid, and reacted at 130 °C for 48 h to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 60 h to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 h, and the product was collected and recorded as MOF-808-Zr-Ac.
[0052] (2) 0.8 g of MOF-808-Zr-Ac prepared in step (1) was placed in 30 mL of methanol solution and soaked for 48 h, filtered and dried to obtain MOF-808-Zr-Me adsorbent.
[0053] Example 5
[0054] A method for preparing a MOF-808-Zr-Me adsorbent comprises the following steps:
[0055] (1) 4 mmol of zirconium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 30 mL of DMF and 15 mL of formic acid, and reacted at 140 °C for 60 h to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 72 h to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 h, and the product was collected and recorded as MOF-808-Zr-Ac.
[0056] (2) 0.8 g of MOF-808-Zr-Ac prepared in step (1) was soaked in 30 mL of methanol solution for 96 h, filtered and dried to obtain MOF-808-Zr-Me adsorbent.
[0057] Comparative Example 1
[0058] A method for preparing a MOF-808-Zr-Ac adsorbent comprises the following steps:
[0059] 3 mmol of zirconium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 15 mL of DMF and 15 mL of formic acid, and reacted at 120°C for 72 hours to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 48 hours to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 hours, and the product was collected to obtain an adsorbent material, which was recorded as MOF-808-Zr-Ac.
[0060] Comparative Example 2
[0061] A method for preparing a MOF-808-Hf-Ac adsorbent comprises the following steps:
[0062] 3 mmol of hafnium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 15 mL of DMF and 15 mL of formic acid, and reacted at 120°C for 72 hours to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 48 hours to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 hours, and the product was collected to obtain an adsorbent material, which was recorded as MOF-808-Hf-Ac.
[0063] Comparative Example 3
[0064] A method for preparing a MOF-808-Ti-Ac adsorbent comprises the following steps:
[0065] 3 mmol of titanium oxychloride and 1 mmol of 1,3,5-tribenzoic acid were dissolved in a mixed solvent of 15 mL of DMF and 15 mL of formic acid, and reacted at 120°C for 72 hours to obtain a slurry. The obtained slurry was filtered, washed, and soaked in acetone for 48 hours to remove the DMF molecules in the structural pores. Then, the slurry was vacuum activated at 373 K for 6 hours, and the product was collected to obtain an adsorbent material, which was recorded as MOF-808-Ti-Ac.
[0066] Application Example 1
[0067] The adsorbent material MOF-808-Zr-Me prepared in Example 1 was loaded into a fixed bed adsorption column with an inner diameter of 6 mm and a length of 15 cm. At 298 K and 1 bar, a C2H2 / CO2 (50:50) mixed gas flowed through the adsorption column at a fixed flow rate of 1.0 or 2.0 mL / min. High-purity C2H2 gas (purity > 99.9%) was obtained at the tail end of the adsorption column. The adsorption was stopped when the adsorption column was completely penetrated. At room temperature, the adsorption column was purged with helium to achieve cyclic regeneration.
[0068] Application Comparative Example 1
[0069] The MOF-808-Zr-Ac prepared in Comparative Example 1 was loaded into a fixed bed adsorption column with an inner diameter of 6 mm and a length of 15 cm. At 298 K and 1 bar, a C2H2 / CO2 (50:50) mixed gas flowed through the adsorption column at a fixed flow rate of 1.0 or 2.0 mL / min. High-purity C2H2 gas (purity > 99.9%) was obtained at the tail end of the adsorption column. The adsorption was stopped when the adsorption column was completely penetrated. At room temperature, the adsorption column was purged with helium to achieve cyclic regeneration.
[0070] Results Analysis
[0071] Figure 1 and Figure 2 The synthetic powder images of the MOF-808-Zr-Ac adsorbent and the MOF-808-Zr-Me adsorbent prepared in Comparative Example 1 and Example 1 of the present invention are shown in FIG. Figure 3 The X-ray diffraction experimental results of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention are as follows: Figure 4 This is the X-ray diffraction experimental result of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention. It can be seen from the figure that the synthesized MOF-808-Zr-Ac adsorbent has good crystallinity. At the same time, there is not much difference between the MOF-808-Zr-Me after methanol immersion and the original sample. The results show that the immersion does not significantly change the framework structure of MOF-808-Zr-Ac.
[0072] Figure 5 This is the adsorption isotherm of C2H2 and CO2 of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention at 298K. It can be seen from the figure that the adsorption amounts of C2H2 and CO2 of the material at 298K and 1bar are 1.78mmol / g and 1.27mmol / g, respectively. The results show that MOF-808-Zr-Ac thermodynamically exhibits preferential adsorption of C2H2 and cannot directly purify C2H2 from the CO2 / C2H2 mixed gas. Figure 6 This is the adsorption isotherm of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention for C2H2 and CO2 at 298K. It can be seen from the figure that the adsorption amounts of CO2 and C2H2 by MOF-808-Zr-Me at 298K and 1bar are 3.56mmol / g and 1.58mmol / g, respectively. The results show that MOF-808-Zr-Me has the ability to preferentially adsorb CO2 thermodynamically and has the potential to directly purify C2H2 from a CO2 / C2H2 mixed gas.
[0073] Figure 7This is the dynamic penetration curve of the C2H2 / CO2 mixed gas component (volume ratio 1:1, flow rate 2.0 mL / min) of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention at 298 K. It can be seen from the figure that CO2 is detected at the outlet at 10 min / g, while C2H2 is detected at about 15 min / g. The results show that MOF-808-Zr-Ac can only collect a small amount of CO2 with relatively high purity after 10 min / g, and cannot obtain high-purity C2H2. Figure 8 This is the dynamic penetration curve of the C2H2 / CO2 mixed gas component (volume ratio 1:1, flow rate 2.0 mL / min) of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention at 298 K. It can be seen from the figure that C2H2 is detected at the rear end of the penetration column at 10 min / g, and CO2 is detected at around 43 min / g. The results show that MOF-808-Zr-Me can collect high-purity C2H2 (>99.9%) during 10 min / g to 43 min / g, and has the ability to directly purify C2H2 from the CO2 / C2H2 mixed gas.
[0074] Fig. 9 This is the dynamic penetration curve of the C2H2 / CO2 mixed gas component (volume ratio 1:1, flow rate 1.0 mL / min) of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention at 298 K. It can be seen from the figure that when the flow rate is reduced, C2H2 is detected at the rear end at around 30 min / g, and CO2 is detected at around 112 min / g, which is twice higher than that at a flow rate of 2 mL / min. The results show that a reduction in flow rate is beneficial to the separation of CO2 / C2H2 gases by MOF-808-Zr-Me.
[0075] Fig.10 This is the acid-base stability test result of the MOF-808-Zr-Ac adsorbent prepared in Comparative Example 1 of the present invention. It can be seen from the figure that when MOF-808-Ac is placed in air or pH = 5-9 solution, no obvious decrease in crystallinity is found. When the pH is further increased or decreased, a significant decrease in crystallinity is observed. The results show that the material has good acid-base and air stability. Fig.11 This is the acid-base stability test result of the MOF-808-Zr-Me adsorbent prepared in Example 1 of the present invention. It can be seen from the figure that when MOF-808-Ac is placed in air or pH=3-9 solution, no obvious decrease in crystallinity is found. A significant decrease in crystallinity is observed when the pH is further increased or decreased. The results show that MOF-808-Zr-Me has better acid-base and air stability.
[0076] In summary, the adsorbent material prepared by the present invention, due to the particularity of its structure after being soaked in methanol, shows a stronger affinity for CO2, while its effect on C2H2 is weakened, which solves the problem that the conventional MOFs material adsorbs more C2H2 than CO2, and can only obtain CO2 through desorption, resulting in low yield and low gas purity, and the conventional MOF-808-M-Ac does not have the ability to preferentially capture CO2 between C2H2 and CO2.
[0077] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing an adsorbent, characterized in that: The following steps are involved: Using 1,3,5-tribenzoic acid as a ligand, tetravalent transition metal chloride oxide as a node coordination, and DMF and formic acid as a mixed solvent, a reaction is performed to obtain a slurry, and the slurry is post-treated to obtain a product; The adsorbent is obtained by soaking the product in methanol.
2. The method for preparing an adsorbent according to claim 1, characterized in that: The tetravalent transition metal is one of Zr, Hf and Ti.
3. The method for preparing an adsorbent according to claim 1, characterized in that: The molar ratio of the tetravalent transition metal chloride oxide to 1,3,5-tribenzoic acid is 2-4:1, the volume ratio of DMF to formic acid is 1-2:1, the mass ratio of the product to methanol is 0.8 g:30 mL, and the amount ratio of 1,3,5-tribenzoic acid to the mixed solvent is 1 mmol:30-45 mL.
4. The method for preparing an adsorbent according to claim 1, characterized in that: The reaction temperature is 120-140° C., the reaction time is 48-72 hours, and the methanol soaking time is 48-96 hours.
5. The method for preparing an adsorbent according to claim 1, characterized in that: The post-treatment step is: filtering the slurry, soaking it in acetone for 48 to 72 hours, and then performing vacuum activation.
6. An adsorbent obtained by the preparation method according to any one of claims 1 to 5.
7. Use of the adsorbent according to claim 6 in selectively adsorbing CO2 to separate and purify C2H2, characterized in that: The application method is: contacting the mixed gas of C2H2 and CO2 with the adsorbent in the adsorption column, adsorbing CO2 in the mixed gas, and obtaining C2H2 with a purity greater than 99.9%.
8. The use according to claim 7, characterized in that: In the mixed gas, the volume fraction of C2H2 is 1%-99%.
9. The use according to claim 7, characterized in that: The adsorption temperature is -50 to 150°C, and the adsorption pressure is 0 to 10 bar.
10. The use according to claim 7, characterized in that: The contact mode between the mixed gas and the adsorbent is one of fixed bed adsorption, fluidized bed adsorption and moving bed adsorption, and the contact adsorption process is one or more of a single-tower or multi-tower pressure swing adsorption process, a temperature swing adsorption process and a vacuum adsorption process.
